The lacuna : a novel - Kingsolver, Barbara (New York : Harper, 2009)
"The story of Harrison William Shepherd, a man caught between two worlds -- Mexico and the United States in the 1930s, '40s, and '50s -- and whose search for identity takes readers to the heart of the twentieth century's most tumultuous events"--Provided by publisher.
Keywords: Americans -- Mexico -- Fiction; Identity -- Fiction; Subversive activities -- Fiction; Mexico -- History -- 1910-1946 -- Fiction; North Carolina -- History -- 20th century -- Fiction; Biographical fiction; Historical fiction; Epistolary fiction